GC/MS evaluation of compounds in dry and conditioned Striga species seeds - Rugutt, J.K.; Irani, R.J.; Fischer, N.H.; Berner, D.K.; McCarley, T.D. (American Chemical Society, 1996)
We have analyzed the dichloromethane (CH2Cl2) extracts of seeds of dry and conditioned Striga hermonthica (Del.) Benth., S. aspera (Willd.) Benth., and S. gesnerioides (Willd.) Vatke by means of gas chromatography (GC) coupled to mass spectrometry (MS). Sixteen compounds were identified on the basis of their mass spectra and their retention indices. All Striga spp. extracts contained tetradecanoic acid, cis,cis-9,12-octadecadienoic acid, cis-9-octadecenoic acid, and sitosterol. Also, 2,6-dimethoxy-p-benzoquinone (2,6-DMBQ) and several long chain aldehydes and n-hydrocarbons were detected in some of the extracts. The nature of the chemical changes induced by seed conditioning is discussed.